2019
DOI: 10.1177/0733464819894542
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Self-Employed When Heading for Retirement

Abstract: Self-employment allows individuals to extend their working lives instead of accepting forced retirement. This study examines transitions to self-employment after age 50 but before retirement age. The study is based on data from Survey of Health, Ageing and Retirement in Europe (SHARE), in which 16,412 people from 18 countries contributed 24,583 observations. Multilevel analyses were used; the data were pooled into one dataset, in which individuals (first-level variables) were nested within countries (second-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…SHARE was established as a longitudinal study meant to shed light on the changing demographic, health and economic trends in Europe (Achdut et al, (2015); Katz et al, 2015; Tur‐Sinai & Litwin, 2015; Lowenstein et al, 2019; Tur‐Sinai et al, 2019b). Within this ambit, men and women aged 50+ as well as their spouses were interviewed (Axelrad & Tur‐Sinai, 2020; Shuldiner et al, 2020; Silverstein et al, 2020; Tur‐Sinai et al, 2019a; Tur‐Sinai & Lewin‐Epstein, 2020). In addition SHARE End‐of‐Life survey, a complementary survey was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHARE was established as a longitudinal study meant to shed light on the changing demographic, health and economic trends in Europe (Achdut et al, (2015); Katz et al, 2015; Tur‐Sinai & Litwin, 2015; Lowenstein et al, 2019; Tur‐Sinai et al, 2019b). Within this ambit, men and women aged 50+ as well as their spouses were interviewed (Axelrad & Tur‐Sinai, 2020; Shuldiner et al, 2020; Silverstein et al, 2020; Tur‐Sinai et al, 2019a; Tur‐Sinai & Lewin‐Epstein, 2020). In addition SHARE End‐of‐Life survey, a complementary survey was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Within this ambit, men and women aged 50+ as well as their spouses were interviewed (Axelrad & Tur-Sinai, 2020;Shuldiner et al, 2020;Silverstein et al, 2020;Tur-Sinai et al, 2019a;. In addition SHARE End-of-Life survey, a complementary survey was conducted.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…Most studies focus only on employees, who may be pushed out of the labour force by law (Henretta, 2018) or by labour agreements. The self-employed, in contrast, have the freedom to choose the timing of their retirement (Lobley et al, 2016;Axelrad and Tur-Sinai, 2021). Unless the analysis focuses on specific sectors of the labour market (or includes a comparison with the self-employed; Wahrendorf et al, 2017), employment is defined in general termswhether one is employed, even for very few hours a week or less, or not.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…These three factors can be further categorized as push factors such as anxiety, pull factors such as job satisfaction, barriers that prevent retirement, enabling factors that promote retirement transition such as pension benefits and trigger factors that force individuals to retire before their retirement age. Axelrad and Tur-Sinai (2019) found out that few employees between the ages of 50 and 60 in the formal sector may decide to switch to the informal sector to become self-employed workers'. The study identified that health limitations, marital status and national unemployment affect workers' ability to switch from salaried work to self-employment.…”
Section: Determinants Of Retirement Planningmentioning
confidence: 99%